2021
DOI: 10.1002/adsc.202101098
|View full text |Cite
|
Sign up to set email alerts
|

Site‐Selective 1,4‐Difunctionalization of Nitrogen Heteroaromatics for Constructing Vinylidene Heterocycles

Abstract: A one-pot protocol for constructing 1,4difunctionalized quinoline/pyridine derivatives via the reaction of N-heteroaromatics, alkyl halides, and active methylene/methyl compounds was developed. The transformation involves dearomative functionalization of an in situ-activated N-heteroaromatic to construct new CÀ N and C=C bonds. This reaction has a broad substrate scope and functional group tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Based on the results of the control experiment and previous studies, a preliminary reaction strategy was employed. First, nucleophilic reactions occur between 1a and 3a to form 1A , and then 2b enamine attacks 1A to form 1A-1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of the control experiment and previous studies, a preliminary reaction strategy was employed. First, nucleophilic reactions occur between 1a and 3a to form 1A , and then 2b enamine attacks 1A to form 1A-1 .…”
Section: Resultsmentioning
confidence: 99%
“…The challenges for developing this method include: (1) constructing spiro[pyridine-thiazolane] ring derivatives with complex structures using a one-pot approach, (2) achieving the dearomatization and spirocyclization of 2-methylbenzo-thiazolium salts, and (3) performing the reaction without transition metal catalysis. Building upon our previous research on nitrogen heterocycle synthesis, this study demonstrated a tandem spirocyclization reaction of 2-methylbenzo-thiazolium salts, which enables the preparation of various structurally novel spiro[pyridine-thiazolane] ring derivatives without using transition metal catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Chen and Zhu reported a three-component 1,4-difunctionalization reaction of quinoline and pyridine derivatives by means of their reaction with alkyl halides and active methylene/methyl compounds ( Scheme 217 ). 290 Thus, the solvent free reaction of quinolines 2 , benzyl bromides 323 and nitromethane under oxygen atmosphere in the presence of Cs 2 CO 3 as a base afforded 1,4-dihydroquinolines 450 by means of a dearomative functionalization of the in situ -activated quinoline ( Scheme 217 , eq 1). Various quinolines bearing electron-withdrawing and/or electron-donating groups participated in this reaction, as well as pyridines bearing strongly electron-withdrawing groups (NO 2 or CN) at the 3-position.…”
Section: Addition Of Other Nucleophilesmentioning
confidence: 99%
“…In addition, indoles have been widely used as important nucleophiles in various synthesis reactions. , The nucleophilic dearomatization reaction of this type of reagent with isoquinolines to efficiently synthesize 1,2-disubstituted isoquinolinones has important research value. Based on our interest in the construction of novel nitrogen heterocycles and the recent advances in the quinoline dearomatization reaction, we report herein a multi-component tandem reaction involving the construction of new C–N, C–C, and CO bonds to synthesize isoquinolinone skeletons with indole groups in one pot.…”
Section: Introductionmentioning
confidence: 99%